Allopurinol reduces B-type natriuretic peptide concentrations and haemoglobin but does not alter exercise capacity in chronic heart failure. (13th May 2005) - Gavin, A D; Struthers, A D
Abstract : Objective: To study whether the effect of allopurinol on improvement of endothelial dysfunction in chronic heart failure (CHF) translates into improved exercise capacity and to examine whether allopurinol also improves B-type natriuretic peptide (BNP), the other important prognostic marker of CHF. Design: Randomised, double blind, placebo controlled crossover trial. Setting: Teaching hospital. Patients: 50 patients with CHF (New York Heart Association functional classes II and III) were recruited. Interventions: 50 patients with CHF were randomly assigned to three months' treatment with allopurinol (300 mg/day) or placebo. At two and three months into treatment, they underwent a modified Bruce exercise protocol and a six minute walk test. Blood was taken for BNP and haemoglobin analysis. Results: Neither exercise test was altered by allopurinol. However, plasma BNP concentrations fell significantly (p  =  0.035) with allopurinol (11.9 pmol/l) versus placebo (14.4 pmol/l). Haemoglobin concentrations also fell highly significantly with allopurinol (p  =  0.001). Conclusions: An important negative finding is that despite high hopes for it, allopurinol had no effect on exercise capacity in CHF. On the other hand, allopurinol did reduce BNP, which is the best available surrogate marker for prognosis in CHF.